Evolution from estuary to delta: Alluvial plain morphology and sedimentary characteristics of the Shoalhaven River mouth, southeastern Australia. (5th September 2020) - Carvalho, Rafael C.; Woodroffe, Colin D.
Abstract: The Shoalhaven River in southern New South Wales (NSW) drains a catchment of 7000 km 2, forming a barrier estuary at its mouth with a prograded strandplain to its north. Previous coring and dating across the floodplain and adjacent strandplain indicate progressive infill of the estuarine basin over the past 7000 years. Over this time the system transitioned from a wave-dominated estuary to a wave-dominated delta. The Shoalhaven River appears to have initially discharged to the sea at Crookhaven Heads, until it adopted a more direct route through an intermittently open mouth at Shoalhaven Heads; construction of Berrys Canal in 1822 now permanently links the Shoalhaven River to the adjacent smaller Crookhaven River. Airborne LiDAR reveals details of topography of prominent levees and meander scroll bars that flank the lower reaches of the river and beach/foredune ridges to the north. Sedimentological and mineralogical characteristics of modern sediment samples collected from the river channel, the beach, and the barrier reveal that the Shoalhaven River is dominated by quartz sand along its predominantly straight course through the infilled estuarine plains. This is in contrast to the tripartite classification of sedimentary depositional environments, comprising sandy fluvial delta, central mud basin, and sandy marine barrier, that characterised the initial wave-dominated estuary 7000 years ago, and is typical of most barrier estuaries in NSW. Grain size decreases downstream and sands have a higher feldspar content, and angularity, than is typical of marine sand that has been reworked in the nearshore. This fluvially-derived component is delivered to the coast intermittently by floods that re-open Shoalhaven Heads, as shown by retrospective analysis of aerial photography and satellite imagery. Grain size decreases with distance alongshore from the river mouth indicating that these sands are transported north by longshore drift to augment a gradual onshore delivery of sand within this coastal compartment. Scanning electron microscopy of selected grains implies that this fluvial sand has been contributing to incremental formation of beach ridges for much of the past 3000 years since the estuarine basin has been largely infilled, with a slight detectable acceleration in the rate of progradation. Highlights: Shoalhaven River has changed from barrier estuary to wave-dominated delta. Infilled estuarine channel in former mud basin is now dominated by sands. Fluvially-derived sediments are intermittently delivered to the coast by flood events. Angular terrestrial sand has augmented progradation of adjacent strandplain.